2020
DOI: 10.1002/mgg3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Modifier genes in SCN1A‐related epilepsy syndromes

Abstract: Background: SCN1A is one of the most important epilepsy-related genes, with pathogenic variants leading to a range of phenotypes with varying disease severity. Different modifying factors have been hypothesized to influence SCN1A-related phenotypes. We investigate the presence of rare and more common variants in epilepsy-related genes as potential modifiers of SCN1A-related disease severity. Methods: 87 patients with SCN1A-related epilepsy were investigated. Whole-exome sequencing was performed by the Beijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…However, there have been reports of Dravet syndrome caused by SCN1A variants inherited from mildly affected parents, as well as some individuals with de novo loss-of-function or premature truncation variants that presented with milder phenotypes, like generalized epilepsy with febrile seizures plus (GEFS + ) (Depienne et al 2010 , 2009 ; Goldberg-Stern et al 2014 ; Guerrini et al 2010 ; Nabbout et al 2003 ; Osaka et al 2007 ; Yordanova et al 2011 ; Yu et al 2010 ). This variable expressivity suggests that disease severity is influenced by additional factors, which may include genetic modifiers (de Lange et al 2020 ; Hammer et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been reports of Dravet syndrome caused by SCN1A variants inherited from mildly affected parents, as well as some individuals with de novo loss-of-function or premature truncation variants that presented with milder phenotypes, like generalized epilepsy with febrile seizures plus (GEFS + ) (Depienne et al 2010 , 2009 ; Goldberg-Stern et al 2014 ; Guerrini et al 2010 ; Nabbout et al 2003 ; Osaka et al 2007 ; Yordanova et al 2011 ; Yu et al 2010 ). This variable expressivity suggests that disease severity is influenced by additional factors, which may include genetic modifiers (de Lange et al 2020 ; Hammer et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the same variant may lead to GEFS+ or in few cases to DS [Helbig, 2015;Scheffer and Nabbout, 2019]. It has been reported that the phenotypic heterogeneity observed in cases with the same variant may be associated with modifier genes and somatic mosaicism [Goldberg-Stern et al, 2014;Myers CT et al, 2018;de Lange et al, 2020]. Wholeexome sequencing analyses performed in cases with variations in the SCN1A gene showed that patients had a milder clinical picture when they had variations in other epilepsy-associated genes such as SCN8A, SCN9A, MOCS2, RAI1, and KMT2A in addition to the variation in SCN1A [de Lange et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…This combination could perhaps explain the milder phenotypes. Furthermore, cases with variations in KCNQ3 and TSC2 genes exhibited a more severe epilepsy phenotype [de Lange et al, 2020]. Moreover, the parents of DS cases with de novo truncation variants in the SCN1A gene have somatic mosaicism, and they show a milder phenotype [de Lange et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Indeed genetic background has been shown to influence disease severity in DS, 7 whereas evidence for specific modifier genes has emerged. 18 In some cases variants in other ion channels have been shown to be associated intra-familial variability in phenotype severity, for example, in SCN9A, 22 CACNA1A, 23 CACNB4, 24 and KCNQ2. 7 Here we study a four-generation family kindred in which a single pathogenic variant is segregating among multiple members with a range of severities ranging from unaffected carriers to febrile seizures to DS.…”
Section: Discussionmentioning
confidence: 99%